Altered Gray-Matter Volumes Associated With Betel Quid Dependence - Yuan, Fulai; Kong, Lingyu; Zhu, Xueling; Jiang, Canhua; Fang, Changyun; Liao, Weihua (Frontiers in Psychiatry, 2017)
Betel quid (BQ) is one of the most commonly consumed psychoactive substances. It has been suggested to be associated with various health issues, especially oral cancer. Evidence also points to possible decreased cognitive functions after long-term BQ chewing, such as attention and inhibition control. The present study aimes to investigate the brain structure basis of BQ chewing in Hunan province of China. Twenty-five BQ chewers and 25 controls were recruited to participate in this study. Voxel-based morphormetry analysis revealed that there were three key regions showing structural differences between BQ chewers and controls, including bilateral DLPFC/Insula, VMPFC, and left OFC. Moreover, the GMV in the DLPFC could potentially predict BQ dependence scores, level of daily BQ chewing, and history of BQ chewing. These results suggested that participants who showed BQ chewing dependence may have deficit in inhibition control and affective decision making, and the level of deficit was dependent on the level of daily BQ chewing, and history of BQ chewing. Understanding the neurobiology features of BQ chewing would help us develop novel ways to diagnose and prevent BQ dependence.